Is transcatheter aortic valve implantation (TAVI) a cost-effective treatment in patients who are ineligible for surgical aortic valve replacement? A systematic review of economic evaluations. (May 2014) - Eaton, James; Mealing, Stuart; Thompson, Juliette; Moat, Neil; Kappetein, Pieter; Piazza, Nicolo; Busca, Rachele; Osnabrugge, Ruben
Abstract Objectives: Health Technology Assessment (HTA) agencies often undertake a review of economic evaluations of an intervention during an appraisal in order to identify published estimates of cost-effectiveness, to elicit comparisons with the results of their own model, and to support local reimbursement decision-making. The aim of this research is to determine whether Transcatheter Aortic Valve Implantation (TAVI) compared to medical management (MM) is cost-effective in patients ineligible for surgical aortic valve replacement (SAVR), across different jurisdictions and country-specific evaluations. Methods: A systematic review of the literature from 2007–2012 was performed in the MEDLINE, MEDLINE in-process, EMBASE, and UK NHS EED databases according to standard methods, supplemented by a search of published HTA models. All identified publications were reviewed independently by two health economists. The British Medical Journal (BMJ) 35-point checklist for economic evaluations was used to assess study reporting. To compare results, incremental cost effectiveness ratios (ICERs) were converted to 2012 dollars using purchasing power parity (PPP) techniques. Results: Six studies were identified representing five reimbursement jurisdictions (England/Wales, Scotland, the US, Canada, and Belgium) and different modeling techniques. The identified economic evaluations represent different willingness-to-pay thresholds, discount rates, medical costs, and healthcare systems. In addition, the model structures, time horizons, and cycle lengths varied. When adjusting for differences in currencies, the ICERs ranged from 27K–65K per QALY gained. Conclusions: Despite notable differences in modeling approach, under the thresholds defined by using either the local threshold value or that recommended by the World Health Organization (WHO) threshold value, each study showed that TAVI was likely to be a cost-effective intervention for patients ineligible for SAVR.